2020
DOI: 10.3390/ijerph17061828
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Prediction with Machine Learning Methods among Older Chinese

Abstract: Timely stroke diagnosis and intervention are necessary considering its high prevalence. Previous studies have mainly focused on stroke prediction with balanced data. Thus, this study aimed to develop machine learning models for predicting stroke with imbalanced data in an elderly population in China. Data were obtained from a prospective cohort that included 1131 participants (56 stroke patients and 1075 non-stroke participants) in 2012 and 2014, respectively. Data balancing techniques including random over-sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 33 publications
0
40
2
Order By: Relevance
“…When working with imbalanced data, SMOTE resampling often achieves better performance in predicting stroke occurrence [ 34 ]. However, investigating important features with synthetic data maybe not be persuasive because of its nature of linear interpolation.…”
Section: Discussionmentioning
confidence: 99%
“…When working with imbalanced data, SMOTE resampling often achieves better performance in predicting stroke occurrence [ 34 ]. However, investigating important features with synthetic data maybe not be persuasive because of its nature of linear interpolation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the reported prediction models for IS diagnosis mostly relied on the conventional statistical models. For example, Cox proportional hazard model uses selected features for the prediction of disease occurrence, which is hard to predict discrete events and has a relatively low efficiency [7,8]. Therefore, to improve subjective decision making in resource-limited settings, a paradigm change from reactive medicine to PPPM/3PM is needed [9].…”
Section: Challenges In Triaging Patients With Ischemic Strokementioning
confidence: 99%
“…It has also been shown that ML methods perform poorly on imbalanced datasets, as they will be biased towards the majority group [59,87,88]. In other words, insufficient training samples and imbalanced class distribution will limit predictive performance in cases of rare occurrences [89].…”
Section: Application Developmentmentioning
confidence: 99%